Qasd and Qusud in Magasidi Thought and Phenomenology: Contexts and Outcomes - Bouhanneche, Noura (Journal of Contemporary Maqasid Studies, 2023)
Linking between maqasid and phenomenology is considered a very daring and exciting task, as it will carry the field of Maqasid, with its referential and methodological weight, to modernity, especially the reframing, of Maqasid on rationality. This opens questions of criticism, suspicion, and doubt, then analysis and simplification, to comply with Cogito whose basis is human Ego and pure rationality, with a goal to obtain an abstract understanding of the Essence. In this space, Hassan Hanafi introduced an initiative to open up to the rational cosmic, by reintroducing a renewal of Maqasid, according to the epistemological and methodological approach of phenomenology. He supported his views based on commonalities with Maqasid however, this approach revealed some contradictions which did not allow him to get to the desired conclusion. This is because abstract rationality will never accommodate the rationality of the Testimony, (al-Shahadah) just as the purposes of Maqasid are defined in the practical legitimacy, while the abstract epistemological concern is essential in phenomenology. So, the results of the modernization work of the Maqasid were irrelevant, as it is a typical reincarnation of modernity that is not compatible with Islamic thoughts as a whole.